Endovascular treatment for left innominate vein aneurysm: Case report and literature review - Gaopo Cai; Zhaohui Hua; Peng Xu; Zhouyang Jiao; Hui Cao; Shirui Liu; Jing Yuan; Zhengyu Peng; Zhen Li (Journal of Interventional Medicine, 2019)
Innominate vein aneurysms originating from the mediastinum are very rare. Previous treatments for this condition often required thoracotomy. We report a case of a 43-year-old male who presented a mediastinal mass by chest radiography. Contrast-enhanced CT and venography confirmed the diagnosis of left innominate vein aneurysm. The patient underwent endovascular treatment with stent placement and coil embolization of the left innominate vein. The patient remains well 18 months after surgery. The objective of this report is to discuss the diagnosis and endovascular treatment results of innominate vein aneurysm and to review the relevant literature to enhance and expand the pool of knowledge for this abnormality. Keywords: Innominate vein aneurysm, Endovascular treatment, Literature review